Effects of Elevated Atmospheric CO sub(2) on Fine Root Production and Activity in an Intact Temperate Forest Ecosystem - Matamala, Roser; Schlesinger, William H (Global change biology, 2000)
We investigated the effects of elevated atmospheric CO sub(2) concentrations (ambient + 200 ppm) on fine root production and soil carbon dynamics in a loblolly pine (Pinus taeda) forest subject to free-air CO sub(2) enrichment (FACE) near Durham, NC (USA). Live fine root mass (LFR) showed less seasonal variation than dead fine root mass (DFR), which was correlated with seasonal changes in soil moisture and soil temperature. LFR mass increased significantly (by 86%) in the elevated CO sub(2) treatment, with an increment of 37 g(dry weight) m super(-2) above the control plots after two years of CO sub(2) fumigation. There was no long-term increment in DFR associated with elevated CO sub(2), but significant seasonal accumulations of DFR mass occurred during the summer of the second year of fumigation. Overall, root net primary production (RNPP) was not significantly different, but annual carbon inputs were 21.7 gC m super(-2) y super(-1) (68%) higher in the elevated CO sub(2) treatment compared to controls. Specific root respiration was not altered by the CO sub(2) treatment during most of the year; however, it was significantly higher by 21% and 13% in September 1997 and May 1998, respectively, in elevated CO sub(2). We did not find statistically significant differences in the C/N ratio of the root tissue, root decomposition or phosphatase activity in soil and roots associated with the treatment. Our data show that the early response of a loblolly pine forest ecosystem subject to CO sub(2) enrichment is an increase in its fine root population and a trend towards higher total RNPP after two years of CO sub(2) fumigation.